Quality Factor Analysis of Business Profit with Company Value as A Moderating Variable - Deni Sunaryo (CV ODIS, 2022)
This study aims to determine the effect of Profitability, Leverage, and firm age on earnings quality with firm value as a moderating variable. This research uses the object of the banking sub-sector Company, Southeast Asia, for the period 2012-20 20. The data collected is secondary data using the documentation method of company annual reports. The analytical tool used to test the hypothesis is IBM SPPS V2 5. The sampling method used is the sampling technique purposively obtained 11 companies with 99 sample data. The analytical technique used is descriptive statistical analysis, classical assumption test, moderated regression analysis, multiple linear regression, t-test, and f-test. The results partially conclude that Profitability has no significant effect on earnings quality, Leverage has no significant effect on earnings quality, and firm age has no significant impact on earnings quality. The study's results simultaneously showed that the calculated F-value was 0.580 and the F table was 2.7 0, meaning F-value < F-table or a significant value of 0.630 > 0.05. Thus, Profitability, Leverage, and firm age simultaneously have no significant effect on earnings quality. Research results moderated regression analysis (MRA) show that firm value does not moderate profitability on earnings quality, firm value does not moderate leverage on earnings quality, and firm value does not moderate the Company's age on the quality of earnings